KONTRIBUSI DAYA LEDAK OTOT LENGAN DAN KOORDINASI MATA TANGAN TERHADAP KETEPATAN SERVIS ATAS BOLAVOLI MAHASISWA PENDIDIKAN KEPELATIHAN OLAHRAGA UNIVERSITAS RIAU - Ardiah Juita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
Problems in this research originated from field observations showing that volleyball players often failed to serve accurately to the intended target, which was presumed to be influenced by explosive arm muscle power and hand–eye coordination. This study aimed to determine the magnitude of the contribution of explosive arm muscle power and hand–eye coordination to service accuracy among students of Sports Coaching Education at Universitas Riau. The research employed a correlational design. The population consisted of 52 Sports Coaching Education students, and through purposive sampling, 25 students who were able to perform overhead serves were selected as samples. Data were collected using a medicine ball test to measure explosive arm muscle power, the Ballwerfen und Fangen test to assess hand–eye coordination, and a service accuracy test. Data analysis was conducted using simple and multiple product-moment correlation as well as coefficient of determination to identify the level of contribution. The results showed a significant relationship between explosive arm muscle power and service accuracy with an r-count of 0.428 greater than r-table 0.396 and a contribution of 18.28%. A significant relationship was also found between hand–eye coordination and service accuracy with an r-count of 0.411 greater than r-table 0.396 and a contribution of 16.91%. Furthermore, there was a significant combined relationship between explosive arm muscle power and hand–eye coordination with service accuracy, indicated by an R-count of 0.533 greater than R-table 0.396, with a total contribution of 28.44%.